Big Five Personality dengan Agresivitas pada Remaja - Fitri Yolanda (Psyche 165 Journal, 2020)
The purpose of this study is to learn about the differences between the five big personalities and aggressiveness in adolescents. The study was conducted with a quantitative method involving 160 adolescents, including 101 adolescent boys and 59 adolescent girls. Data analysis was performed with multiple regression to test the hypothesis in this study. From the results of the analysis found a significant effect between big five personality with aggressiveness in adolescents (0.014, 0.001, 0.001). The higher the neuroticism, agreeableness and conscientiousness, the aggressiveness will be high, and vice versa, the lower the neuroticism, agreeableness and conscientiousness, the aggressiveness will be low, while extraversion, and openness to experience negatively correlate to aggressiveness, if the higher the extraversion and openness to experience, the aggressiveness will be low, while extraversion, and openness to experience negatively correlate to aggressiveness, low, and vice versa the lower the extraversion, and openness to experience the aggressiveness will be high.